INFLUENCE OF SOME PHENOLOGICAL FACTORS ON THE CARYOPHYLLAEID CESTODE LYTOCESTUS PARASITISING FRESHWATER FISH CLARIAS BATRACHUS (LINNAEUS) - R. T. PAWAR,; N. K. RAUT,; A. B. CHINDURWAR,; C. J. HIWARE, (The Bioscan, 2011)
The present communication deals with the study of the influence of temperature, humidity and rainfall on the incidence of infection of the cestode parasite, Lytocestus parasitising the air breathing freshwater predatory fish, Clarias batrachus (Linnaeus) and results showed pronounced impact on the cestode parasite infection collected from three districts of Marathwada Region Viz. Aurangabad, Parbhani and Nanded for the period of one year (December 2003 to November 2004). The values for percentage of incidence, intensity, density and index of infection were also seen throughout the study period.